ANALISIS PENGARUH KINERJA LINGKUNGAN DAN KINERJA KEUANGAN TERHADAP PENGUNGKAPAN LAPORAN KEBERLANJUTAN PADA PERUSAHAAN NONKEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tusiyati Tusiyati (Jurnal Bina Akuntansi, 2019)
This study aimed to determine the impact of environmental performancemeasured by PROPER (Program Penilaian Peringkat Kinerja Perusahaan dalamPengelolaan Lingkungan Hidup) and financial performance on disclosure ofsustainability report. Sustainability Report (SR) measured by 46 items disclosurestated on G4 GRI (2013), while financial performance measured by using ratio ofprofitability, liquidity, and leverage of non-financial companies listed inIndonesian Stock Exchange and located in DKI Jakarta. A stastistical methodused in this study is multiple regression analysis to examine the effect ofenvironmental performance on the disclosure of sustainability report. Dataanalysis and hypothesis testing in this study using SPSS version 20. Resultsshowed: (1) environmental performance the company has a significant positiveeffect on the disclosure of sustainability report, (2) financial performance has asignificant negative effect on the disclosure of sustainability report.